The Treatment of Curiosity in Strategic Documentation a Study of the Articulation of the New Zealand Curriculum Value of Curiosity by Schools - Binns, Marina Catherine (Auckland University of Technology, 2021)
A significant focus of futures-oriented education is to promote and nurture curiosity. There is a strong consensus between published literature and research findings that curiosity is beneficial and plays a significant part in student achievement. Through the promotion of curiosity, students are prepared to ask and answer questions about things they do not know. Discovering the answers to these questions leads to both individual growth and the expansion of a collective knowledge and understanding, shared within and beyond the formal school context. Curiosity has been included in the New Zealand Curriculum since 2007. This research study addressed the issue of the definition and justification of the inclusion of curiosity as a value in the Curriculum. To achieve this intention, a review was undertaken of how curiosity is defined and described in publicly available school strategic documentation, and interviews conducted with Principals who had indicated that they value curiosity in their schools. An in-depth picture of how curiosity is treated and justified was developed through the study. It was found that curiosity is both difficult to define, and poorly represented in school documentation. The interview participants, nonetheless, argued that curiosity is worth encouraging for its benefits to both students and society. Curiosity does have a place in educational pedagogy and practice and it is important that it continues to be signposted by its inclusion in The New Zealand Curriculum (2007). Schools should, however, explicitly plan for curiosity, acknowledging the importance of learning over performance, by promoting and encouraging students to explore and expand their knowledge of the world and their place in it. Doing so will help their students to adapt to a future made up of uncertain economic situations, external societal pressures and improve their individual achievement.
Keywords: Curiosity; Strategic Documentation; Values education; Curious; New Zealand Curriculum